Code-Switching Dynamics in Bilingual Digital Gaming Interactions - Anggiana Yulyanti; Lusiana Suciati Dewi (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
This study examines code-switching, or language mixing, in a bilingual individual while playing video games. The aim is to determine which types of code-switching are used and the subject's thought process when engaging in this behaviour. This study employed a qualitative case study design involving one participant (the game streamer). Data were collected by recording the participant's spontaneous, unscripted conversations during gameplay, followed by a semi-structured interview to corroborate and clarify the findings. The research results indicate that the subject employed four methods of code-switching: switching languages between sentences, inserting English words into Indonesian sentences, using short interjections, and combining English words with Indonesian affixes (such as “nge-burst” or “boss-nya”). From the interview, it was revealed that the subject had been accustomed to using English for 8 years, so that gaming terms came to mind automatically without prolonged thought. In conclusion, code-switching in the gaming world does not indicate that the subject is not fluent in Indonesian, but rather represents a strategy to communicate more quickly and accurately. English is used for matters of game logic and strategy, while Indonesian remains the subject's primary language of choice for expressing feelings honestly. This study demonstrates that hobbies such as playing video games are highly effective in helping an individual to master a foreign language naturally.